Exploring the Influential Factors of Knowledge Sharing in Virtual Communities in Disaster Events: A Systematic Review - Hasan, Mahmudul; Che Mohd Yusoff, Rasimah; Maarop, Nurazean; Mohd Sam, Suriani; Megat Mohd Zainuddin, Norziha (International Journal of Engineering and Technology, 2018)
Amid any debacle occasions, learning sharing assumes an essential job. The significance of learning sharing among exploited people is recognized in the catastrophe the board writing. Very little research has been done to look at information sharing conduct and not very many investigations have analyzed this conduct from the fiasco the board point of view. Thus, to guarantee a superior comprehension of this conduct, this investigation has directed a methodical writing survey to investigate the compelling elements of information sharing conduct in virtual networks in a fiasco occasions. An orderly procedure has been done to look six noteworthy scholarly databases for this survey.Two hundred eighty-four studies were identified as 21 fulfilled the inclusion criteria and were used for synthesis. The factors in this study include trust, self-efficacy, reciprocity, reputation, rewards, enjoy helping, sharing culture, attitude toward knowledge sharing and knowledge sharing intention. This paper proposes a conceptual model to represent the influential factors identified. Â Â